2016
DOI: 10.18535/jmscr/v4i12.123
|View full text |Cite
|
Sign up to set email alerts
|

A Comparative Study of Maternal and Foetal Outcomes in Patients Undergoing Elective or Emergency Caesarean Section

Abstract: 3%). The most common risk factor is Previous LSCS. 42(28%) patients Elective C-section and 21(14%) patients in Emergency C-section had previous LSCS. BMI of 63 patients in Elective C-S was ranging between 24.9-29.9kg/m2 when compared to only 35 patients with similar BMI in Emergency C-S. Overweight patients underwent more Elective C-S when compared to Emergency C-S. There is a reduction of Hb% in both elective and emergency groups after caesarean section. In Elective Csections, the indications in 47(31.3%), 17… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
13
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(15 citation statements)
references
References 15 publications
2
13
0
Order By: Relevance
“…The similar results were reported in a study conducted by Nag et al [26], who observed intra-operative adhesions in 44.8% of elective cesarean sections and 37.6% of emergency cesarean sections. On the contrary, in a study done by Renuka and Suguna [31], complications other than intra-operative adhesions were not reported. About 12% (24/200) of women had PPH which is similar to the percentage of women with PPH i.e., 8.3% (13/300) in a study conducted by Renuka and Suguna [31] and 12.6% (43/340) cases of PPH in a study by Darnal and Dangal.…”
Section: Discussionmentioning
confidence: 80%
See 1 more Smart Citation
“…The similar results were reported in a study conducted by Nag et al [26], who observed intra-operative adhesions in 44.8% of elective cesarean sections and 37.6% of emergency cesarean sections. On the contrary, in a study done by Renuka and Suguna [31], complications other than intra-operative adhesions were not reported. About 12% (24/200) of women had PPH which is similar to the percentage of women with PPH i.e., 8.3% (13/300) in a study conducted by Renuka and Suguna [31] and 12.6% (43/340) cases of PPH in a study by Darnal and Dangal.…”
Section: Discussionmentioning
confidence: 80%
“…On the contrary, in a study done by Renuka and Suguna [31], complications other than intra-operative adhesions were not reported. About 12% (24/200) of women had PPH which is similar to the percentage of women with PPH i.e., 8.3% (13/300) in a study conducted by Renuka and Suguna [31] and 12.6% (43/340) cases of PPH in a study by Darnal and Dangal. Out of 24 cases of PPH, 83.3% (20/24) were in emergency cesarean section and 16.7% (4/24) were in elective cesarean section.…”
Section: Discussionmentioning
confidence: 80%
“…In the present study, median APGAR score at 1 minute was 7 in all the three groups (normal vaginal delivery group, elective and emergency caesarean groups). The study by Renuka et al at a medical college hospital Khammam reported that the Apgar score of <7 at 1 minute, was present in 16.3% of (n=25) of new born in elective caesarean sections and 18.3% (n=28) in emergency caesarean sections [10] . In our study also, mean and median APGAR score at 1 minute was similar and comparable indicating good practices during operative deliveries.…”
Section: Discussionmentioning
confidence: 99%
“…However, ndings from this study contrast with ndings from Finland, India, Norway, Israel and South Africa which showed emergency CS, cervical dilatation, maternal characteristics and fetal factor were associated with all complications. (11,22,24,29).However, this serves as a continuous alarm to physicians to modify the already known risk factors before surgery to minimize incidences of complications while optimizing good maternal-fetal outcomes.…”
Section: Discussionmentioning
confidence: 99%